Perubahan Sistem Struktur Bangunan Rumah Bugis Sulawesi Selatan - H Hartawan; Bambang Suhendro (Faculty of Engineering, Universitas Gadjah Mada, 2015)
A structural system determines the strength of the building in order to be able to survive in the long period of time. Functioning as residential house, Bugis houses have been through a long period of time and are supported by the use of specific structural system of the building. This structural system has changed in many ways and forms. This research is aimed at identifying the changes that have occurred in the structural system of old Bugis houses and factors that influence such changes. This research employed descriptive models and typology. Descriptive models were used to reveal the phenomenon of point movement of the structural system aided by SAP 2000 software. Typology was used to classify the types of changes that occurred in the system. The research revealed that the structural system of building of Bugis houses has changed by means of cross and internal system. The system used in the past had lower strength than that used in the next period. The characteristics of the changes in the structural system improved by means of transfer of the use of the construction method from the use of free placement to the use of stiff connection. This change was influenced by three aspects, namely of natural resource aspect, stiffness aspect, and cultural and belief aspects. The natural resource aspect is related to the availability of building materials in terms of quality and quantity. The building of Bugis houses in the past used higher quality materials than the system that developed afterwards. The stiffness is related to the efforts of Bugis technocrats in the past in optimizing the structural system. The results of the analysis indicated that the extent of the horizontal of a point movement is in proportion to the height of point position of the structural system. The higher the location, the greater the movement. The culture and belief are related to the survival for individual and group.Keywords: changes, structural system, Bugis houses